Approximation of (ψ, β)-Differentiable Functions Defined on the Real Axis by Abel-Poisson Operators - Zhyhallo, T. V.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We obtain asymptotic equalities for upper bounds of approximations of functions on the classes \(C_β ,∞ ^ψ\) and \(L_β ,1^ψ\) by Abel-Poisson operators.